Hypoxia Inducible Factor-1α Regulates the Migration of Bone Marrow Mesenchymal Stem Cells via Integrin α4 - Jong Ho Choi; Yun Bin Lee; Jieun Jung; Seong Gyu Hwang; IL-Hoan Oh; Gi Jin Kim (Stem Cells International)
Although hypoxic environments have been known to regulate the migratory ability of bone marrow-derived mesenchymal stem cells (BM-MSCs), which is a critical factor for maximizing the therapeutic effect, the underlying mechanisms remain unclear. Therefore, we aimed to confirm the effect of hypoxia-inducible factor-1α (HIF-1α) on the migration of BM-MSCs and to analyze the interaction between HIF-1α and integrin-mediated signals. Hypoxia-activated HIF-1α significantly increased BM-MSC migration. The expression of integrin α4 was decreased in BM-MSCs by increased HIF-1α under hypoxia, whereas the expression of Rho-associated kinase 1 (ROCK1) and Rac1/2/3 was increased. After downregulation of HIF-1α by YC-1, which is an inhibitor of HIF-1α, BM-MSC migration was decreased via upregulation of integrin α4 and downregulation of ROCK1 and Rac1/2/3. Knockdown of integrin α4 by integrin α4 siRNA (siITGA4) treatment increased BM-MSC migration by upregulation of ROCK1, Rac1/2/3, and matrix metalloproteinase-2 regardless of oxygen tension. Moreover, siITGA4 treatment increased HIF-1α expression and augmented the translocation of HIF-1α into the nucleus under hypoxia. Taken together, the alternative expression of HIF-1α induced by microenvironment factors, such as hypoxia and integrin α4, may regulate the migration of BM-MSCs. These findings may provide insights to the underlying mechanisms of BM-MSC migration for successful stem cell-based therapy.